NILAI DAN FUNGSI TARI LENGGANG NYAI - Restuningrum, Ayu; Hartono, Hartono; Lanjari, Restu (Jurnal Seni Tari, 2017)
ABSTRACT   Lenggang Nyai Dance is a dance of new creations created by Wiwiek Widiyastuti in 2002 consists of 32 motions. The idea of creating the Lenggang Nyai Dance is the Nyai Dasimah folklore. This study aims to know and understand, about the values and functions that contained in Lenggang Nyai Dance.  This study uses qualitative method. Data collection techniques that used in this study are observastion, interviews, and documentation. Lenggang Nyai Dance has 2 values, consisting of moral and aesthetic values. Lenggang Nyai Dance has 2 values and 3 functions which is a positive thing for the art connoisseur. The moral values in the Dance Lenggang Nyai in the form of: confusion, sadness, shame, confidence, happiness, confidence, courage, and true love. And the value of aesthetics can be seen from various elements such as wiraga, wirama, wirasa, wirupa. Functions that exist in Lenggang Nyai dance are entertainment, performing arts and as a education facility. Suggestions from the study results are for artists in the future to convey the content of dances and dancers can better appreciate the values that exist in the contents of the dance.   Keyword: presentation form, function, value, Tari Lenggang Nyai